Impact of night shift work on women's fertility, pregnancy and menopause - Lee, Christina Y.; Moawad, Katherine; Pien, Grace W. (Frontiers in Sleep, 2025)
A growing body of literature examines how shift work affects different aspects of women's reproductive cycles, ranging from fertility to pregnancy to menopause. This review summarizes what is known about how shift work affects women's reproductive cycles, with a particular emphasis on fertility, fecundity and the impact of shift work on maternal and fetal outcomes. While the overall impact of night shift work is complex and remains incompletely understood, evidence suggests that shift work adversely impacts reproductive health and pregnancy outcomes.